OPTIMALISASI UNIT PENGOLAHAN SAMPAH ORGANIK MENGGUNAKAN MAGGOT DI TPA MANGGAR KOTA BALIKPAPAN - Rina Noor Hayati; Basransyah; Chandra S. Rahendaputri; Cut Keumala Banaget; Ismi Khairunnissa Ariani; Nadya Misdiana Putri; Ieke Wulan Ayu (SPECTA Journal of Technology, 2026)
The problem of organic waste management in Balikpapan City is increasing, with a total of 193,038 tons/year, 70.3% of which comes from household waste. One solution implemented at Manggar Municipal Solid Waste (MSW) Landfill in Balikpapan is the processing of organic waste using maggots (BSF larvae). This study aims to analyze the current conditions, analyze the factors influencing waste processing, and formulate strategies for optimizing the processing facility. The methods used include quantitative and qualitative approaches, as well as best practice analysis as a basis for improvement. The research findings highlight several issues, such as the absence of BSF egg weighing, predator disturbances in the fly cages, biopon systems without drainage channels, and the manual process of separating maggots from casings. Optimization was carried out through the redesign of the BSF fly enclosure, improvement, and addition of 21 biopon units, which can produce 35.7 liters of liquid organic fertilizer (POC) and decompose 1,0878 tons of organic waste per cycle, the design of a sieving machine, and the reorganization of the maggot house layout. These efforts are expected to enhance processing efficiency and capacity to 1,0878 tons per cycle, supporting more sustainable and environmentally friendly waste management.